Dampak penggunaan media sosial terhadap gangguan kecemasan pada remaja - Zulfa, Intan Nala (Maliki Interdisciplinary Journal, 2024)
This study aims to explore the impact of social media use on anxiety disorders among adolescents using a qualitative approach. The research method employed is in-depth interviews with ten adolescents aged 15-18 who are active social media users. Participants were selected through purposive sampling to ensure they had relevant experiences related to the research topic. The collected data were analyzed using thematic analysis to identify emerging themes and patterns. The results indicate that social media use significantly contributes to increased anxiety levels among adolescents. The most influential factors include the pressure to appear perfect, social comparison, and cyberbullying. Adolescents often feel anxious about others' judgments and the number of "likes" or comments they receive on their posts. Additionally, constant access to social media content leads to inadequate rest and sleep, further contributing to increased anxiety. This study suggests the need for education and awareness regarding healthy social media use and the development of effective coping strategies to mitigate its negative effects. Interventions from parents, schools, and the government are crucial to support adolescents' mental health in the digital age.